2003
DOI: 10.1007/s00520-003-0481-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome after chemotherapy for lung metastases from non-seminomatous germ-cell tumors

Abstract: Acute respiratory distress in patients with lung metastases from NSGCT is a rare cause of ARDS. Chemotherapy could be responsible for triggering the respiratory worsening. Patients with severe respiratory insufficiency (PaO2 <70 mmHg on room air) on admission to hospital should be promptly transferred to the ICU for the first chemotherapy course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 25 publications
2
33
1
Order By: Relevance
“…Therefore we consider that chemotherapy was responsible for triggering hemorrhage. The authors also concluded that patients with moderate hypoxemia (PaO 2 [70 mmHg) could receive the first chemotherapy on a general ward, while more severely hypoxemic patients should be transferred to the ICU [10].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore we consider that chemotherapy was responsible for triggering hemorrhage. The authors also concluded that patients with moderate hypoxemia (PaO 2 [70 mmHg) could receive the first chemotherapy on a general ward, while more severely hypoxemic patients should be transferred to the ICU [10].…”
Section: Discussionmentioning
confidence: 99%
“…All of our three patients became severely ill with acute renal failure, acute respiratory failure, and shock. Kirch and colleagues[4] reported 16 patients with germ-cell tumors with diffuse pulmonary metastases who developed acute respiratory failure following the start of chemotherapy. Out of them, nine required mechanical ventilation and all but one patient died.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it remains unclear whether chemotherapy-associated processes may also be involved in the pathogenesis of these 'tumor-associated' ARDS cases. A recent case series from Kirch et al [5] reported 16 patients with non-seminomatous germ cell tumors and lung metastases who were admitted to the ICU for respiratory distress. In this patient cohort, 9 patients (56%) developed ARDS requiring mechanical ventilation within a median of 2.5 days only after the initiation of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only case reports or small retrospective single-center case series (e.g. from the 'Institut Gustave Roussy') have reported a 'tumor-associated' acute respiratory distress syndrome (ARDS) in patients with non-Boeck/Metzeler/Hausmann/Baumann/ Gallmeier/Parhofer/Stemmler seminomatous germ cell tumors and lung metastases [3][4][5]. Some authors also hypothesized a possible aggravation of acute pulmonary failure by chemotherapy-induced/-associated inflammatory processes and tumor lysis [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation